2005
DOI: 10.1007/s00535-004-1535-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the stent placement above the intact sphincter of Oddi against malignant bile duct obstruction

Abstract: Placement of the stent above the intact sphincter of Oddi was associated with longer stent patency and lower occlusion rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 17 publications
1
50
1
Order By: Relevance
“…However, the migration rate of stents placed above the sphincter of Oddi was 58% in their study. On the other hand, Uchida et al reported that the median patency duration of stents placed above the sphincter of Oddi was superior to that of stents placed across the sphincter of Oddi (255 vs. 82 days), and the respective occlusion rates were 37.5% and 93.8% [15]. Although their results with respect to stent patency were satisfactory, endoscopic sphincterotomy was required for stent exchange in most cases of stent occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the migration rate of stents placed above the sphincter of Oddi was 58% in their study. On the other hand, Uchida et al reported that the median patency duration of stents placed above the sphincter of Oddi was superior to that of stents placed across the sphincter of Oddi (255 vs. 82 days), and the respective occlusion rates were 37.5% and 93.8% [15]. Although their results with respect to stent patency were satisfactory, endoscopic sphincterotomy was required for stent exchange in most cases of stent occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Placement of PS above the sphincter of Oddi (inside stents) was reportedly superior to conventional PS with respect to stent patency in cases of malignant bile duct obstruction [15]. However, another study showed that placement of the inside stent was associated with high rates of stent migration and occlusion [16].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study by Uchida et al. evaluated intraductal PS placement for the treatment of malignant common bile duct obstruction and found that PS placed inside bile ducts remained patent significantly longer than when the PS was placed across the sphincter of Oddi .…”
Section: Discussionmentioning
confidence: 99%
“…Since disruption of the sphincter of Oddi (by passage of a stent across it) allows the ascension of micro-organisms (with subsequent colonization of the endoprosthesis), it may be feasible to reduce bacterial colonization by positioning stents above the sphincter, thus allowing it to function normally. There are clinical data that suggest that stents positioned in this manner have longer patency rates and lower failure rates; however, the numbers of patients in this study were very small (n = 16) [53].…”
Section: Plastic Stentsmentioning
confidence: 94%